IMPLEMENTASI TERAPI MUROTTAL UNTUK MENGONTROL HALUSINASI PENDENGARAN PADA PASIEN SKIZOFRENIA - Rizal faris Nur Zayyan; Arni Nur Rahmawati; Ita Apriliyani (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Mental disorders are stressors that can cause changes in a person's thinking, perception, behavior, and feelings. Schizophrenia is a psychotic mental disorder that has positive, negative, and cognitive signs and symptoms. The World Health Organization in 2021 stated that the prevalence of schizophrenia in the world increased to 26 million people. Hallucinations are one of the symptoms of mental disorders where a person experiences changes or disturbances in sensory perception involving the five senses. The most common hallucination is auditory hallucination. One of the non-pharmacological treatments that can be done in patients with auditory hallucination is Murottal Therapy. Murottal therapy is a therapy by reading or listening to Al-Qur'an. The purpose of this study was to obtain an overview of the nursing process regarding the application of murottal therapy as an effort to control auditory hallucination. The research method used is a case study with the target of schizophrenia patients with auditory hallucinations at Banyumas Hospital. After Murottal Therapy for 6 days, the results showed that the patient could control his hallucinations as evidenced by the Auditory Hallucination Rating Scale score which decreased, score of 22 on the first day and a score of 10 on the sixth day. Therefore, it can be concluded that Murottal Therapy Surah Ar-Rahman verses 1-78 which is performed once a day for 6 days with a duration of 16 minutes, has proven effective for controlling auditory hallucinations in schizophrenic patients.